Building Social-Ecological Resilience in Batukaras Coastal Tourism Village, Indonesia - Ade Tri Putra (Politeknik Negeri Bali, 2026)
Batukaras Village in Cijulang District, Pangandaran Regency, is known as a beach tourism area, as mandated by Village Regulation No. 5 of 2020, aiming to establish itself as an integrated and leading tourist destination. However, climate change and the intensification of coastal activities have increased pressure on marine resources and accelerated coastal environmental degradation. These conditions have created challenges that threaten ecological balance, local livelihoods, and the long-term sustainability of tourism. This study explores socio-ecological responses to environmental and social disruptions in Batukaras. Using a qualitative case study approach, data were collected through observation, documentation, literature review, and in-depth interviews with key informants. The analysis adopts a Social-Ecological Resilience (SER) framework to understand community adaptive capacities and institutional responses. Data analysis combined SER indicators with triangulation techniques to describe patterns of environmental change and socio-ecological interactions within the coastal tourism area based on observed phenomena. The phenomenon examined is the increasing socio-ecological vulnerability in Batukaras resulting from climate change, intensified coastal tourism activities, and tsunami hazards. The study identifies local adaptive responses, including efforts to coexist with environmental changes and limited governmental initiatives promoting ecosystem protection and social equity. In-depth interviews involved nine key informants, including village officials, tourism actors, community leaders, and local residents. To enhance resilience, the study recommends improving resource management, strengthening stakeholder participation in sustainable tourism planning, reinforcing collaborative governance, and integrating local knowledge into policy design to support long-term community welfare, adaptive capacity, disaster preparedness, and environmental sustainability.